2015
DOI: 10.1007/s10620-015-3870-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Impact of Renal Dysfunction in Acute Liver Failure on the US Liver Transplant Waiting List

Abstract: Background & Aims Although renal dysfunction is a known complication of acute liver failure (ALF), its frequency, severity and impact among patients with ALF on the US liver transplant list are not well defined. Methods Organ Procurement and Transplantation data for ALF patients listed as status 1/1A from 2002–2012 were analyzed. The frequency and severity of renal dysfunction at the time of listing [the latter was categorized in 5 stages using estimated GFR (eGFR) according to Chronic Kidney Disease Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…In the univariate (unadjusted) analysis, we showed that the overall characteristics of the TFS group at 21 days post-study enrollment differed from patients who underwent LT or died in demonstrating less severe organ failures (requirement for mechanical ventilation, vasopressors, or renal replacement therapy), lower MELD scores and less frequently demonstrating high grade (III-IV) hepatic encephalopathy. These findings are in keeping with previous reports stating that the prognosis of patients with ALF largely depends on the severity of organ failures that ensues 24, 25 …”
Section: Discussionsupporting
confidence: 93%
“…In the univariate (unadjusted) analysis, we showed that the overall characteristics of the TFS group at 21 days post-study enrollment differed from patients who underwent LT or died in demonstrating less severe organ failures (requirement for mechanical ventilation, vasopressors, or renal replacement therapy), lower MELD scores and less frequently demonstrating high grade (III-IV) hepatic encephalopathy. These findings are in keeping with previous reports stating that the prognosis of patients with ALF largely depends on the severity of organ failures that ensues 24, 25 …”
Section: Discussionsupporting
confidence: 93%
“…It is not surprising to find renal injury as an independent predictor of 28‐day mortality of HEV‐LF, complying with prior studies . Furthermore, Urrunaga et.al not only found that renal dysfunction complicating ALF predicted a significantly worse outcome, but also emphasized the association between mortality and the degree of renal dysfunction . Accordingly, underlying kidney diseases might pre‐dispose HEV‐LF patients to subsequent multiorgan failure in the context of severe liver injury, which definitely led to high mortality.…”
Section: Discussionsupporting
confidence: 56%
“…These abnormalities result in the activation of vasoconstrictor systems through the renin-angiotensin-aldosterone system and of the sympathetic nervous system, with increased levels of antidiuretic hormone and renal vasoconstriction that culminate in ascites and/or edema[46]. These altered physiological states limit the application of available methods to evaluate nutritional status[47].…”
Section: Discussionmentioning
confidence: 99%